Packet guide to Voice over IP - Hartpence, Bruce (O'Reilly, 2013)
Go under the hood of an operating Voice over IP network, and build your knowledge of the protocols and architectures used by this Internet telephony technology. With this concise guide, you'll learn about services involved in VoIP and get a first-hand view of network data packets from the time the phones boot through calls and subsequent connection teardown. With packet captures available on the companion website, this book is ideal whether you're an instructor, student, or professional looking to boost your skill set. Each chapter includes a set of review questions, as well as practical, hands-on lab exercises. Learn the requirements for deploying packetized voice and video Understand traditional telephony concepts, including local loop, tip and ring, and T carriers Explore the Session Initiation Protocol (SIP), VoIP's primary signaling protocol Learn the operations and fields for VoIP's standardized RTP and RTCP transport protocols Delve into voice and video codecs for converting analog data to digital format for transmission Get familiar with Communications Systems H.323, SIP's widely used predecessor Examine the Skinny Client Control Protocol used in Cisco VoIP phones in networks around the world.